Wczesne objawy zakłóceń procesu nabywania systemu językowego - Jagoda Cieszyńska-Rożek (Annales Universitatis Paedagogicae Cracoviensis. Studia Linguistica, 2023)
The article discusses the prodromal signs of language system acquisition disorders, allowing to start early stimulation of infants. The results of the diagnosis of developmental disorders of a group of infants (n=7) from 2 to 6 months of age are presented to which effective auditory and visual stimulation was applied, are presented. The speech development of two neurotypical children stimulated prenatally by the auditory program applied to the infants is presented. These children received the same stimulation in infancy as the children in the experimental group, in order to test its effectiveness. The dynamic speech development of these children made it possible for them to learn to read early using the simultaneous‑sequential method before starting preschool education. The ability to read had a positive impact on intellectual development.